2015
DOI: 10.1016/j.astropartphys.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

First constraints on the ultra-high energy neutrino flux from a prototype station of the Askaryan Radio Array

Abstract: The Askaryan Radio Array (ARA) is an ultra-high energy (> 10 17 eV) cosmic neutrino detector in phased construction near the south pole. ARA searches for radio Cherenkov emission from particle cascades induced by neutrino interactions in the ice using radio frequency antennas (∼ 150 − 800 MHz) deployed at a design depth of 200 m in the Antarctic ice. A prototype ARA Testbed station was deployed at ∼ 30 m depth in the 2010-2011 season and the first three full ARA stations were deployed in the 2011-2012 and 2012… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(108 citation statements)
references
References 38 publications
1
107
0
Order By: Relevance
“…Figure 3: The ARA 2 station neutrino limit for 7.5 months of operation compared to other detector limits and flux expectations. The projection for the ARA37 sensitivity is calculated at trigger level without accounting for systematic errors [9,10,13,14,12,15,16,17,18].…”
Section: Latest Data Analysis Results From Two Ara Stationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3: The ARA 2 station neutrino limit for 7.5 months of operation compared to other detector limits and flux expectations. The projection for the ARA37 sensitivity is calculated at trigger level without accounting for systematic errors [9,10,13,14,12,15,16,17,18].…”
Section: Latest Data Analysis Results From Two Ara Stationsmentioning
confidence: 99%
“…Currently, 3 ARA stations and a prototype are deployed at the South Pole. The prototype station, called Testbed, has been used to determine ice properties for radio measurements and for an initial neutrino search, described in [10]. It was decommissioned in 2013.…”
Section: The Detectormentioning
confidence: 99%
“…Three such repeating locations were identified and geometric cuts were designed to reject events from these locations. Descriptions of further cuts can be found in [8]. After a number of quality cuts, the effective livetime drops to 224 days.…”
Section: Pos(icrc2015)1105mentioning
confidence: 99%
“…This analysis only examines data from March to August 2011. A complete description of these analyses can be found in [8].…”
Section: Testbed Data Analysesmentioning
confidence: 99%
“…Such emission has been measured and characterized at beam-line experiments [4,5,6]. This technique has been exploited by several experiments in Antarctica, including ANITA [7], ARA [8], and ARIANNA [9]. These experiments have thresholds > 50 PeV, however, recent studies have shown improved sensitivity to the PeV energy scale using phased arrays of antennas [10,11], which would complement studies of the few-PeV astrophysical neutrino signal discovered by IceCube [12].…”
Section: Introductionmentioning
confidence: 99%